Comprehensive evaluation of using computerised provider order-entry system for hospital discharge orders. (April 2022) - Colombini, N.; Abbes, M.; Cherpin, A.; Bagneres, D.; Devos, M.; Charbit, M.; Rossi, P.
Highlights: Physicians' adoption of CPOE is high for discharge orders in acute medical care unit. In using CPOE system, prescription error rate in discharge order was 2.3%. Daily pharmacist's interventions contributed in reducing the prescription error rate. Discrepancies in the recording process to discharge summary were frequent. Abstract: Background: Computerised prescriptions for Hospital Discharge Orders (HDO) are used world-wide to secure medication processes. Objectives: To evaluate physicians' adoption of computerised provider order-entry (CPOE) for HDO and the prescribing error rate of HDO in an acute medical care unit. Setting: A prospective study was conducted in an internal medicine department over a six-month period. The use rate of CPOE for HDO edition, prescription lines concordance between CPOE-edited HDO, exit prescriptions transcribed in the discharge summary (DS), and prescribing error rate in CPOE-edited HDO were all evaluated. Results: A total of 407 patients with HDO were included in the study. HDO were edited via CPOE system for 350 patients (86%), among which 124 (35%) were identically transcribed, 217 (62%) had discrepancies, and nine (3%) were not transcribed in the discharge summary (DS). Prescription errors were analysed using the total of 2, 854 drugs prescribed on HDO. Although hospital pharmacists had signalled discrepancies and provided recommendations to the prescribers via alerting pharmaceutical interventions in CPOE 67 prescription errors (error rate of 2.3%) were found. Errors included 53 cases of refractory period disrespected, four cases of drug interactions, three cases of drug redundancies, and two cases of excessive dosage. Conclusion: This study highlights that most HDO were edited via the CPOE system. Together with pharmacist's interventions, the CPOE system contributed to reducing the prescription error rate in HDO. However, discrepancies in the recording process to DS were frequent, calling for reinforcement of error prevention strategies upon the integration of a CPOE system in the hospital's Electronic Health Records. Providing regular training for physicians is also a requirement.